STUDI TENTANG PERGESERAN ADAT PERKAWINAN BUDAYA MELAYU DESA BANTAN TENGAH KECAMATAN BANTAN KABUPATEN BENGKALIS - Ririn Astika; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research with the community met Rural Middle Bantan already left the marriage customs of Malay culture, which leads to a more practical marriage customs. Because they think that by wearing a marriage custom in many the cost is quite large and they are not capable of it. The formulation of the issue in this study is Is there a shift in the customary marriage Malay culture Central District Bantan Bantan Village Bengkalis and what factors cause a shift of Customary Marriages Malay Cultural Village Central District Bantan Bantan District Bengkalis.Bertujuan To determine the shift in the marriage customs Malay culture village Central District Bantan Bantan Bengkalis. For Knowing the factors that cause the shift of Customary Marriages Malay Cultural Village Central District Bantan Bantan Bengkalis. The sample in this study 80 respondents ie Bantan Village Community Central married by using the Malay culture and community leaders .. Using purposive sampling technique with Suharsimi Arikunto. Data were collected through observation, questionnaire, interview, documentation and analysis of data using qualitative descriptive tenik. Question with words is still, what reason and how. Using the formula P = F / N x 100. From the benchmarks, When respondents who answered (Yes) As much as 51% -100% = Not Happen shift. When respondents who answered (Yes) As much as 0% - 50% = There is a shift, and 47% included in the benchmark of 0% -50%. It can be concluded there is a shift of Malay Customary Marriage Middle Village District Bantan Bantan Bengkalis. Factors affecting the shifting Customary Marriages Malay Culture Village Central District Bantan District Bengkalis is Factor from aoutside the community that consistes of changes in the word economy, foreign cultural contact and the influence of foreign cultures So there is a shift in the malay culture Traditional Wedding Village Bantan Tengah Districts Bantan District Bengkalis.Keywords: Shift, Customary Marriage, Malay Culture Village, Central Bantan